Effect of Condensation Pressure on Microleakage of Mineral Trioxide Aggregate - Jalalzade, Seyed Mohsen; Khoshbin, Elham; Tabatabaei, Seyed Abdolkarim; Ansari, Ghassem (Journal of Dental School, 2019)
Objective: The aim of this study was to assess the effect of condensation pressure on microleakage of mineral trioxide aggregate (MTA). Methods: This in vitro experimental study was conducted on 55 sound single-rooted straight-canal extracted human teeth. The teeth were sectioned at the cementoenamel junction (CEJ) and at 3 mm above the root apex. The roots were mounted in putty. Samples were then divided into three experimental groups (n=15) and positive and negative control groups (n=5). After filing of the root canals to file #50, white ProRoot MTA paste was prepared according to the manufacturer’s instruction and applied to the canals using condensation pressure of 0.44, 3.22 and 8.88 Mpa in groups one to three, respectively. After a 48-hour setting time, each root was connected to the fluid filtration system to measure microleakage. The mean microleakage rate of the groups was calculated and compared using one-way ANOVA and least significant difference test. Results: The mean microleakage with condensation pressure of 0.44, 3.22 and 8.88 MPa was 1.70×10-4, 1.17×10-4 and 0.48×10-4 µL/minute, respectively. One-way ANOVA showed that the mean microleakage rate was significantly different among the groups (P<0.05). The lowest microleakage was observed in condensation pressure of 8.88 MPa. Conclusion: Within the limitations of this study, the results showed that increase in condensation pressure decreased the rate of microleakage.